Co-occurring Mental Illness and Substance Use Disorders : a Guide to Diagnosis and Treatment. - Avery, Jonathan D. (American Psychiatric Publishing, 2017)
To help clinicians keep the big picture in mind, the book is organized around 18 cases, each of which addresses a particular diagnostic skill (e.g., assessment), group of disorders commonly comorbid with substance use disorders (e.g., PTSD, eating disorders), specific treatment (e.g., pharmacological interventions), or special population (e.g., adolescents).